DFT study on hydrogen storage of Be or V modified boron-doped porous graphene. (1st November 2022) - Zou, Jiayi; Liu, Ziyi; Ge, Yan; Ding, Jiangyi; Nie, Mingjie; Miao, Zhicheng; Yang, Zhihong; Wang, Yunhui; Bi, Lan
Abstract: Based on density functional theory, the hydrogen storage performance of boron-doped porous graphene modified with beryllium or vanadium metal was studied. By changing the doping amount of boron and the doping sites, it was found that metals have the highest adsorption energy on B16 -PG and B22 -PG doped with a pair of boron atoms and two pairs, respectively. Be2 –B16 -PG and Be2 –B22 -PG can adsorb six hydrogen molecules, the corresponding hydrogen storage capacities are 7.30 wt% and 7.40 wt%, respectively. V2 –B16 -PG can adsorb up to ten hydrogen molecules, with the hydrogen storage energy reaching 8.07 wt%. This shows that boron doping can effectively improve the hydrogen storage performance of the system. Graphical abstract: Image 1 Highlights: The hydrogen storage properties of boron-mixed porous graphene were studied by DFT. Ead (H2 ) of Be2 –B22 -PG are in the range of 0.09–0.30 eV. Ead (H2 ) of V2 –B16 -PG are in the range of 0.34–0.50 eV. The gravimetric capacity of Be2 –B22 -PG system reaches 7.40 wt%. The gravimetric capacity of V2 –B16 -PG system reaches 8.07 wt%.